Deactivation and diffusion of boron in ion-implanted silicon studied by secondary electron imaging - Castell, M; Simpson, T; Mitchell, I; Perovic, D; Baribeau, J (American Institute of Physics, 1999)
Secondary electron (SE) imaging in a scanning electron microscope is used to map electrically active dopant distributions of B-doped superlattices in Si. By comparing SE contrast profiles with secondary ion mass spectroscopy data, it is shown that B is electrically deactivated when the damage caused during Si implantation falls onto a doped region. Following a 450°C anneal, the effect of the implantation damage is severely reduced in the SE profiles and the B is partially reactivated. An 815°C anneal results in transient enhanced diffusion of some of the B with the remainder trapped in an inactive immobile peak.